Potential effects of dietary chitosan against lead-induced innate immunotoxicity and oxidative stress in Nile tilapia (Oreochromis niloticus) - Sally M. Salaah; Dalia M. El-Gaar; Hanan S. Gaber (Egyptian Journal of Aquatic Research, 2022)
Urbanization and industrialization have led to heavy metals in aquatic environments. These metals are toxic, nondegradable, and persistent. Lead (Pb) is an immunotoxicant that can adversely affect animal health, even at low levels. Chitosan (CHI) is an eco-friendly compound with exceptional antibacterial and immunostimulant characteristics. This study investigated the effect of dietary CHI on the antioxidant defense system and innate immune responses of tilapia (Oreochromis niloticus) against the cytotoxic effect of prolonged Pb exposure. The results indicated dietary CHI could nullify the toxicity of prolonged Pb exposure in fish by substantially activating the antioxidant defense system capacity and fish innate immune responses. In addition, CHI minimized the alterations in the histology of fish organs. The findings suggest that chitosan can be a commercial, eco-friendly immunostimulant and bioactive compound for mitigating the effects of heavy metal toxicity in aquaculture.